Contextualizing DepEd AI guidelines in early childhood education practice: Understanding the distinctive context of kindergarten - Hidaya Ampaso Tataan; Juhani M. Dimalna; Ma. Janice R. Gorrero; Nabila P. Lacongan; Twenlie F. Sabanal (Eureka: Journal of Educational Research, 2026)
The Foundational Guidelines on Artificial Intelligence in Basic Education of the Philippine Department of Education (DepEd Order No. 003, s. 2026) is a comprehensive policy framework for the K-12 program. However, the policy recognizes that this policy is “more of a framework and that specific operational and technical guidelines shall be issued separately” (Sections II and V of the policy document). Hence, this study seeks to present some relevant considerations and contextualization that may help in the development of operational guidelines within the realm of early education. It is the contention of the researchers that early childhood education has a unique place in the context of basic education. Using a qualitative descriptive method, which integrates document analysis with a synthesis of previous research studies on the application of AI in early childhood education, the researchers found the following key characteristics of early education that should be noted in the direction of AI policies and trainings: (1) AI use in kindergarten is teacher-mediated rather than learner-driven; (2) developmental appropriateness requires specialized teacher literacy; (3) teacher AI literacy serves as the critical infrastructure for ethical AI integration; (4) cultural and linguistic relevance demands culturally responsive AI competencies; and (5) child data privacy necessitates heightened, practical safeguards. The study concludes with six practical considerations for developing complementary AI guidance tailored to early childhood education, emphasizing teacher capacity, specialized literacy training, culturally relevant resources, simplified data privacy protocols, communities of practice, and accountability aligned with professional growth.